The Role of Parents in Qur'an Memorization Activities at TK Tahfidz Al-Quds Samarinda - Nuriesta Rusjianto Saputri; Nur Kholik Affandi (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the role of parents in Qur’an memorization activities at TK Tahfidz Al-Quds Samarinda. It employs a qualitative research design with a phenomenological approach to understand the experiences and roles of parents as they support their children during the memorization process. Participants were selected using purposive sampling and consisted of guardians of students at TK Tahfidz Al-Quds Samarinda. Data collection involved observation, interviews, and documentation. The results indicate that parental involvement makes a significant contribution to early-childhood Qur’an memorization. Three specific key aspects were identified: the internalization of religious values ​​and goals, parental roles and strategies, and the impact on child development. Parents act as facilitators, monitors, and motivators, supporting memorization through practices such as*muraja’ah (review), talaqqi (direct recitation/instruction), habituation, and integration with play activities, while providing support in the form of dedicated time, private tutors, and audiovisual aids. The impact on child development extends to cognitive, emotional, and moral domains, manifesting as improved memory, emotional regulation skills, and the early cultivation of proper character akhlaq regarding the Qur’an.